Writing A Video Script to Promote DR. A.K. Gani Museum as a Tourism Destination in Palembang - Lidya Ferliana (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
This study was aimed at finding out how to write a video script of dr. A.K. Gani Museum as a tourism destination in Palembang. The researcher used Research and Development (R&D) method by Plomp (1997), consisted of preliminary investigation, designing, realization/construction, testing, evaluation and revision, and implementation. In the preliminary investigation, the researcher did literature and field study. In designing step, the researcher modified video script by Ranga and Koul (2017). Then, in realization/construction step, the researcher made first draft and linked it to AIDA Model stated by Rofiq et al (2012). After that, the researcher did test, evaluation, and revision by giving it to four experts who were chosen purposively (Head of dr. A.K. Gani Museum, Script writer, English linguist, Video Editor). The last step was implementation, in which the result was a final video script entitled â€œVisiting dr. A.K. Gani: Historical Tourism Destination in Palembangâ€. The researcher uploaded the video in social media such as Youtube for promoting Palembang tourism destination.